The impact of storage time on coagulation factor activity in FFP - Gao, Jie; Zhao, Juan; Xu, Luo; He, Rui; Li, Mei; Wang, Li; Liang, Xuemei; Shao, Yan; Chen, Rong; Xian, ChunBo; Li, Ke; He, Rong (Frontiers in Medicine, 2025)
ObjectiveThis research aims to explore the change law of coagulation factor activity in fresh frozen plasma (FFP) with storage time under standard storage conditions, evaluate the quality change characteristics during its validity period, and provide scientific basis for optimizing the inventory management and turnover strategy of fresh frozen plasma in primary hospitals.MethodsFFP under standard storage conditions (≤−18 °C) was followed up for 1 year (from the date of collection), and the activated partial thromboplastin time (APTT), prothrombin time (PT), international normalized ratio (INR) and factor VIII (FVIII) activity at different time points were measured, and the results were analyzed statistically.ResultsThe PT and APTT of FFP showed an upward trend with the extension of storage time, and remained within the normal reference range, but the growth rate of PT increased after more than 300 days. The activity of FVIII decreased by 19.35% compared with the baseline level, and the qualified rate was only 72% after 120 days of storage.ConclusionUnder standard storage conditions, the coagulation function indexes (PT, APTT) of FFP remain normal, but the activity of some coagulation factors (such as FVIII) will decrease significantly with the extension of storage time and inventory management of fresh frozen plasma that been stored nearly 300 days should be enhanced.